EDUKASI POLA HIDUP SEHAT DAN PENCEGAHAN STUNTING BAGI IBU RUMAH TANGGA DI DESA POKURUMBA MELALUI PROGRAM GIZI SEIMBANG - Nasraeni (JESASI (JURNAL EDUKASI, SAINS, DAN INOVASI), 2025)
This study aimed to improve housewives’ knowledge of healthy lifestyles and stunting prevention through a balanced nutrition education program in Desa Pokurumba. Stunting remains a major health problem caused by poor nutrition and unhealthy habits. The program involved 25 housewives selected purposively and implemented through lectures, discussions, and demonstrations using LCD projectors, food pyramid models, and anthropometric measurements. Data were collected before and after the activity using questionnaires and physical measurements, then analyzed descriptively. The results showed an increase in participants’ understanding of balanced nutrition, healthy living, and child growth monitoring. Mothers became more aware of the importance of nutritious food and active lifestyles in preventing stunting. In conclusion, balanced nutrition education effectively enhanced mothers’ awareness and behavior toward healthy living, serving as a practical effort in reducing the risk of stunting in rural communities.